Un siècle d'Arpenteurs : Les Figures de la Marche : De Rodin à Giacometti, De Beuys à Nauman. - Arasse, Daniel; Bourg, Lionel; Davila, Thierry; Falguières, Patricia; Fréchuret, Maurice; Michaud, Eric; Tiberghien, Gilles A.; Exhibition. Les Figures de la Marche : De Beuys à Nauman. Exhibition. Les Figures de la Marche : De Rodin à Giacometti. Musée Picasso Antibes. 2000-07-01. 2000-11-04. 2000-10-15. 2001-01-14 (Antibes Paris : Musée Picasso Antibes Reunion des Musées Nationaux Paris, 2000)
Adams, Dennis ; Agut, Pep ; Alys, Francis ; Andre, Carl ; Bacon, Francis ; Balla, Giacomo ; Beecroft, Vanessa ; Beuys, Joseph ; Bossu, Sylvia ; Brauner, Victor ; Brouwn, Stanley ; Cadere, Andre ; Callahan, Harry ; Cartier-Bresson, Henri ; Case, Charley ; Castellas, Denis ; Cattelan, Maurizio ; Charbonnier, Jean Philippe ; Coplans, John ; Debord, Guy ; Dubuffet, Jean ; Duchamp, Marcel ; Dufrêne, François ; Durham, Jimmie ; Firman, Daniel ; Fleury, Sylvie ; Fulton, Hamish ; García Sevilla, Ferran ; Gasiorowski, Gérard ; Giacometti, Alberto ; Gontcharova, Natalia ; Gordon, Douglas ; Guilleminot, Marie-Ange ; Hains, Raymond ; Hatoum, Mona ; Hélion, Jean ; Huyghe, Pierre ; Hyber, Fabrice ; Jamet, Pierre ; Kertesz, André ; Lacasse, Joseph ; Larionow, Michail ; Leger, Fernand ; Lipchitz, Jacques ; Londe, Albert ; Long, Richard ; Malone, Laurent ; Marey, Etienne-Jules ; Matisse, Henri ; Miro, Joan ; Muybridge, Eadweard James ; Nauman, Bruce ; Orozco, Gabriel ; Pellizza Da Volpedo, Giuseppe ; Prampolini, Enrico ; Richier, Germaine ; Robakowski, Jozef ; Rodchenko, Alexander ; Rodin, Auguste ; Rumney, Ralph ; Sander, August ; Schütte, Thomas ; Seeberger, Albert & Jean ; Shiraga, Kasuo ; Stalker ; Stratmann, Veit ; Tal-Coat, Pierre ; Tàpies, Antoni ; Villeglé, Jacques ; Wall, Jeff ; Zadkine, Ossip
Frans
boek